Effect of Musthadi Rajayapana Vasti in Parkinson’s Disease - Varsha. K; T. K. Sujan; Ambili Krishna; Manju. P.S (International Journal of Ayurveda and Pharma Research, 2022)
Parkinson’s disease is a progressive neurodegenerative disorder, affecting the older adult. It is a syndrome consisting of classical triad of resting tremor, bradykinesia and rigidity. The triad does not include the equally important gait and postural instability problem which also constitute syndrome. Lakshanas of Vata prakopa can be seen in Parkinson’s Disease. Madhavanidana, Vangasena, Sarngadhara samhita, Basavatrajiya has quoted the pathology Kampavata- a disease condition that explains Parkinson’s disease in similar way. In short Parkinson’s disease can be compared to Kampavata. Vasti is Paramoushadha of Vata. To be specific, Musthadi rajayapana vasti is Brimhana and Vatahara in nature. So it is the best choice for a Vatavikara like Parkinson’s disease. Brimhana type of vasti plays an important role, hence Rajayapana vasti. The study is pre-post study. participants registered in IPD and OPD of Govt Ayurveda Panchakarma Hospital, Poojappura satisfying inclusion criteria were selected. After collecting baseline data, detailed history and examination were done using clinical case proforma. 15 participants were selected for the study. Musthadi rajayapana vasti was done continuously for 7 days. Assessment of efficacy was done before Vasti, after Vasti on 8th day and after follow up on 14th day by Unified Parkinson’s Disease Rating Scale. Quantitative and qualitative assessment of Vasti dravya was also done. Data were analysed according to ‘Wilcoxon signed rank test’. Based on statistical analysis Musthadi rajayapana vasti was found to be significant in reducing symptoms. Musthadi rajayapana vasti is effective in reducing severity of symptoms of Parkinson’s disease